As a Staple Food Substitute, Oat and Buckwheat Compound Has Health-Promoting Effects for Diabetic Rats - Liu, Siqi; Yin, Xueqian; Hou, Chao; Liu, Xinran; Ma, Huijuan; Zhang, Xiaoxuan; Xu, Meihong; Xie, Ying; Li, Yong; Wang, Junbo (Frontiers in Nutrition, 2021)
Dietary intervention is crucial to the prevention and control of diabetes. China has the largest diabetic population in the world, yet no one dietary strategy matches the eating habits of the Chinese people. To explore an effective and acceptable dietary pattern, this study uses Oat and Buckwheat Compound (OBC) as a staple food substitute and explored its effects on diabetic Sprague-Dawley rats. The model of diabetic rats was established by combining high-calorie feed and streptozotocin injection. The dietary intervention for the seven groups, including a normal control group, a model control group, a metformin control group, a wheat flour control group, and three OBC groups with different doses, started from the beginning of the experiment and lasted for 11 weeks, two consecutive injections of STZ in small doses were operated at the sixth week. General states, glucose metabolism, and lipid metabolism indexes were measured. Antioxidant and inflammatory indexes and pathologic changes of kidney and liver tissues were tested. Changes in kidney and ileum ultra-microstructure were detected. What’s more, ileal epithelial tight junction proteins and gut microbiota were analyzed. Significant decrease in fasting blood glucose, glucose tolerance, serum insulin, and insulin resistance were observed in rats intervened with OBC, these rats also showed a higher level of superoxide dismutase together with improved lipid metabolism, attenuated inflammation, and liver and kidney injuries. In addition, in OBC groups, the intestinal barrier was improved, and the disturbance of gut microbiota was reduced. These results showed that OBC could improve diabetes, and as oat and buckwheat are traditional consumed grains in China, OBC could be an optimal and easy-to-accept staple food substitute for the dietary pattern for Chinese.